Negotiating femininity: SA teenage girls’ interpretation of teen magazine discourse constructed around Seventeen - De Villiers, Emma (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2009.